Trends in Tinea Capitis in an Irish Pediatric Population and a Comparison of Scalp Brushings Versus Scalp Scrapings as Methods of Investigation. Issue 5 (22nd February 2013) - Nasir, Shaaira; Ralph, Nicola; O'Neill, Charles; Cunney, Robert; Lenane, Patricia; O'Donnell, Brigid
Abstract A retrospective study of 391 children with suspected tinea capitis was analyzed to examine the prevalence of dermatophyte species and to compare the efficacy of the scalp scraping method with that of the hairbrush method for diagnoses over a 6‐year period. Trichophyton tonsurans tinea capitis is the most common pathogen. The hairbrush method of obtaining specimens for fungal culture was superior to scalp scrapings (p = 0.03) in making the diagnosis, and using two methods (p < 0.001) increased the yield of identifying a dermatophyte infection.